The predictive performance of artificial intelligence on the outcome of stroke: a systematic review and meta-analysis - Yang, Yujia; Tang, Li; Deng, Yiting; Li, Xuzi; Luo, Anling; Zhang, Zhao; He, Li; Zhu, Cairong; Zhou, Muke (Frontiers in Neuroscience, 2023)
Objectives: This study aimed to assess the accuracy of artificial intelligence (AI) models in predicting the prognosis of stroke. Methods: We searched PubMed, Embase, and Web of Science databases to identify studies using AI for acute stroke prognosis prediction from database inception to Feb. 2023. Selection studies were designed cohorts and had complete data. We used the Quality Assessment of Diagnostic Accuracy Studies tool to assess the qualities and bias of included studies and used a random-effects model to summarize and analyze the data. We used the area under curve (AUC) as an indicator of the predictive accuracy of AI models. Results: We retrieved a total of 1241 publications and finally included seven studies. There was a low risk of bias and no significant heterogeneity in the final seven studies. The total pooled AUC under the fixed-effects model was 0.872 with a 95% CI of (0.862 - 0.881). The DL subgroup showed its AUC of 0.888 (95%CI 0.872 - 0.904). The LR subgroup showed its AUC 0.852 (95%CI 0.835 - 0.869). The RF subgroup showed its AUC 0.863 (95%CI 0.845 - 0.882). The SVM subgroup showed its AUC 0.905 (95%CI 0.857 - 0.952). The Xgboost subgroup showed its AUC 0.905 (95%CI 0.805 – 1.000). Conclusions : The accuracy of AI models in predicting the outcomes of ischemic stroke is good from our study. It could be an assisted tool for physicians judging the outcomes of stroke patients. With the update of AI algorithms and the use of big data, further AI predictive models will perform better.